1(b-3)=6

Simple and best practice solution for 1(b-3)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1(b-3)=6 equation:


1(b-3)=6

We simplify the equation to the form, which is simple to understand
1(b-3)=6

Reorder the terms in parentheses
+(+1b-3)=6

Remove unnecessary parentheses
+1b-3=+6

We move all terms containing b to the left and all other terms to the right.
+1b=+6+3

We simplify left and right side of the equation.
+1b=+9

We divide both sides of the equation by 1 to get b.
b=9

See similar equations:

| 3y-12+63=180 | | 2x-(-15)=27-4x | | x/7-22=-1 | | 3x-7x-9=4x+4-9 | | (y-7)-(y+5)=8y | | 4-30+5y=45 | | x^2=6.25 | | 2-x=5yz+4 | | x^6-2x^4+4x^2-8=0 | | 1+.8c=7 | | 8x+x=12+104 | | 24+6y=-12 | | 20=2x+12 | | 51pt-3p+4t= | | y=2*1 | | 1x^2-9x-6=0 | | (x^2+6x+5)-(x^2+4x-5)= | | 2y+4=6y | | 4y-4=6y-22 | | (6x)-(x+8)= | | -6=6/5b+5 | | 8(y+5)+y=3(y+3)+2 | | 25-5x-18-12x=0 | | y=1+5 | | 9x-19=2x+11 | | 6x-x=60+30 | | x^2-6x+153=0 | | 16a*2-14a+1a*2-3a= | | 25-5x-18-12x=10 | | x^2-6+153=0 | | 15x+6-(X+2)= | | 0.25(m+5)=-1.5 |

Equations solver categories